2023
DOI: 10.1371/journal.pone.0285891
|View full text |Cite
|
Sign up to set email alerts
|

The impact of government subsidy and weather on environmentally sustainable investment decision for agricultural supply chain

Abstract: This paper studies the environmentally sustainable investment of an agricultural supply chain composed of a farmer and a company, under three subsidy policies which are the non-subsidy policy, the fixed subsidy policy, and the Agriculture Risk Coverage (ARC) subsidy policy. Then, we analyse the impact of different subsidy policy and adverse weather on the costs of the government and profits of the farmer and the company. By comparing with the non-subsidy policy, we find that both the fixed subsidy policy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Mohammadi et al [ 53 ] established a multi-objective mixed integer nonlinear programming model for the sustainable supply chain of perishable products with price-dependent demand and deterioration rate, determined the optimal pricing strategy and cycle length, and achieved profit maximization and specific social goals. Fu et al [ 54 ] discussed the influence of non-subsidy policy, fixed subsidy policy and agricultural risk coverage (ARC) subsidy policy on government costs, farmers and enterprise profits. It is found that the fixed subsidy policy and ARC policy improve the level of farmers’ environmentally sustainable investment and increase the profits of farmers and companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mohammadi et al [ 53 ] established a multi-objective mixed integer nonlinear programming model for the sustainable supply chain of perishable products with price-dependent demand and deterioration rate, determined the optimal pricing strategy and cycle length, and achieved profit maximization and specific social goals. Fu et al [ 54 ] discussed the influence of non-subsidy policy, fixed subsidy policy and agricultural risk coverage (ARC) subsidy policy on government costs, farmers and enterprise profits. It is found that the fixed subsidy policy and ARC policy improve the level of farmers’ environmentally sustainable investment and increase the profits of farmers and companies.…”
Section: Literature Reviewmentioning
confidence: 99%